Risky sexual behaviour and HIV testing uptake among male college students: a cross-sectional study in China - Yan Luo; Gang Zhao; Junfang Xu (BMJ Open)
Objective To understand the sexual behaviours and HIV testing uptake of sexually experienced male college students in China.Design A cross-sectional study was conducted between September and November of 2020 among male college students.Setting Hangzhou, China.Participants Male students who had sexual experience in the previous year were investigated.Outcome measures Sexual risk behaviour was defined as having multiple sexual partners or having unprotected sex.Results More than half of the sexually experienced male students (556, 53.2%) had their first sexual intercourse under the age of 18 years old. Among participants, 32.82% (343/1045) had causal sex in the last 6 months; 4.21% (44/1045) had paid sex; 37.32% (390/1045) had sex with other men and had two or more sexual partners in last half year; and 33.33% (130/390) used psychoactive drugs during same-sex intercourse. Only 33.5% (350/1045) of male students had undertaken an HIV test before.Conclusion Male college students especially men who have sex with men were at risk because they tended to be sexually adventurous, have sex at an early age, have sex with multiple sexual partners and practice unprotected sex. Furthermore, they had a low HIV testing uptake. This highlights the importance of carrying out targeted and timely HIV risk education towards college students.